Analysis And Planning of An Integrated Service Information System At The Home Autis Center Medan - Gabriel Ardi Hutagalung; Ari Syaiful Rahman Arifin (Jurnal Mantik, 2026)
This study aims to analyze the requirements and design a web-based integrated service information system for Home Autis Center Medan, a therapy institution that provides intervention services for children with Autism Spectrum Disorder (ASD). The analysis was conducted on the existing manual system, which resulted in data duplication, recording errors, and inaccurate service scheduling. Based on the findings, a system design was developed, including system architecture, database structure, process workflows, and user interface design. The proposed system planning encompasses features for student data management, learning goals management, therapy activity recording, and real-time web-based child development reporting. The result of this study is a blueprint or system design ready for implementation, which is expected to improve administrative efficiency, reduce recording errors, accelerate the reporting process, and support the implementation of good service governance at Home Autis Center Medan